Exam Management System for the Mathematics Department, Faculty of Science, Khon Kaen University. - Thanaphawa, Theeradech (KKU Science Journal, 2025)
This research aims to (1) develop an examination management system for the Mathematics Department, Faculty of Science, Khon Kaen University, and (2) enhance the efficiency of managing examination paper sets and packaging using a digital platform based on the System Development Life Cycle (SDLC) approach. The web application was developed using PHP and MySQL as the database management system to resolve problems associated with manually written examination cover sheets, which often result in errors, missing information, and formatting inconsistencies. The developed system enables exam scheduling, automatically generates examination cover sheets, supports direct printing on exam envelopes, and provides real-time status reports. Additionally, it features automated notifications via Line Application and email to enhance communication and operational efficiency. The research results revealed that the developed system effectively supported four distinct user groups: system administrators, exam committee staff, course instructors, and departmental members. Each group was granted specific access rights to ensure security. The system reduced errors, simplified complex processes, and improved convenience in accessing data according to user roles. Overall user satisfaction was rated as very high, with an average score of 4.73 (94.60%) and a standard deviation of 0.46. Future recommendations for system development include integrating features for tracking the status and location of exam envelopes, setting up alerts for late exam manuscript submissions, enabling instructors to verify exam sets before packaging, and linking exam envelope management data with other departments to enhance overall operational efficiency.